2020
DOI: 10.1007/s12079-020-00566-3
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin-1 and fibrillin-1-derived asprosin in adipose tissue function and metabolic disorders

Abstract: The extracellular matrix microenvironment of adipose tissue is of critical importance for the differentiation, remodeling and function of adipocytes. Fibrillin-1 is one of the main components of microfibrils and a key player in this process. Furin processing of profibrillin-1 results in mature fibrillin-1 and releases the C-terminal propeptide as a circulating hunger hormone, asprosin. Mutations in the fibrillin-1 gene lead to adipose tissue dysfunction and causes Marfan syndrome, marfanoid progeroid lipodystr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 139 publications
(222 reference statements)
0
46
0
Order By: Relevance
“…One may predict that all these proteins are required for effective SARS-CoV-2 development; thus, down-regulation of their genes might cause lower susceptibility to COVID-19. The FBN1 gene codes for fibrillin-1, a protein which is proteolytically cleaved to generate an extracellular matrix glycoprotein and asprosin, involved in glucose homeostasis [21]. MFGE8 also codes for a polyprotein which after cleavage is converted into several polypeptides, among which lactahedrin is the major one; lactahedrin is a membrane glycoprotein promoting phagocytosis of apoptotic cells [22].…”
Section: Resultsmentioning
confidence: 99%
“…One may predict that all these proteins are required for effective SARS-CoV-2 development; thus, down-regulation of their genes might cause lower susceptibility to COVID-19. The FBN1 gene codes for fibrillin-1, a protein which is proteolytically cleaved to generate an extracellular matrix glycoprotein and asprosin, involved in glucose homeostasis [21]. MFGE8 also codes for a polyprotein which after cleavage is converted into several polypeptides, among which lactahedrin is the major one; lactahedrin is a membrane glycoprotein promoting phagocytosis of apoptotic cells [22].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it appears that the balance between adipokines contributes to the maintenance of homeostasis [7]. In reference, the literature reports that mutations in some of the genes result in increased TGF-β signaling, altered mechanical properties, impaired adipogenesis, leading to adipose tissue dysfunction and giving rise to many conditions, such as Marfan syndrome, marfanoid progeroid lipodystrophy syndrome and neonatal progeroid syndrome [8]. The need to explore this topic led to the discovery of a new adipokine.…”
Section: Characteristics Of Asprosinmentioning
confidence: 99%
“…[8]. Single injection of recombinant asprosin leads to immediate increase of both blood glucose and insuline, but all study so far shows that asprosin does not directly affect insulin production in the pancreas [7] [8]. Some reaserches suggested that exercise could also affect the levels of asprosin.…”
Section: Characteristics Of Asprosinmentioning
confidence: 99%
See 2 more Smart Citations